TRAM deletion attenuates monocyte exhaustion and alleviates sepsis severity - Wang, Jing; Wu, Yajun; Lin, RuiCi; Zhang, Yao; Li, Liwu (Frontiers in Immunology, 2023)
Monocyte exhaustion characterized by immune-suppressive features can develop during sepsis and contribute to adverse patient outcomes. However, molecular mechanisms responsible for the establishment of immune-suppressive monocytes with reduced expression of immune-enhancing mediators such as CD86 during sepsis are not well understood. In this study, we identified that the TLR4 intracellular adaptor TRAM plays a key role in mediating the sustained reduction of CD86 expression on exhausted monocytes and generating an immune-suppressive monocyte state. TRAM contributes to the prolonged suppression of CD86 through inducing TAX1BP1 as well as SARM1, collectively inhibiting Akt and NFκB. TRAM deficient mice are protected from cecal slurry-induced experimental sepsis and retain immune-competent monocytes with CD86 expression. Our data reveal a key molecular circuitry responsible for monocyte exhaustion and provide a viable target for rejuvenating functional monocytes and treating sepsis.